Learning Through Experience:Making Sense of Students’ Learning through Service Learning - Gredley, Sue (South African Journal of Higher Education, 2016)
Service learning is often heralded as an important way of providing potentially transformative learning opportunities for students to develop empathy and an ethic of care, contributing to student ‘being’ and engagement in the world. However, many scholars have noted that service learning does not inherently and by itself offer students the space to explore their personal responses to the challenges of service work. This can result in service that embeds and perpetuates hierarchy and difference. My research paid more explicit attention to student ‘being’ to explore learnings about self, knowledge and practice. Through data that included interviews, reflective writing and online blogs, I tracked the learning journeys of four students through a service learning course that aims to foreground values and ‘being’. I asked how this focus on ‘being’ affected the students’ learning. I found that through “learning service” (Boyle-Baise et al. 2006) ‘being’ was transformed for each student, which resulted in changed ‘knowing’ and practice.